1999
DOI: 10.1046/j.1440-1754.1999.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of growth on development outcome in extremely low birthweight infants at 2 years of age

Abstract: Low weight percentile at 2 years was related to adverse developmental outcome in ELBW infants at high perinatal risk or with neurological impairment, though minimal association was present for neurologically normal infants at low perinatal risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 28 publications
2
7
0
2
Order By: Relevance
“…Early introduction and faster advancement of feeds lead to a faster regaining of birthweight between 11 and 18 days (7,9,13). It also shows better catch-up growth, linear growth and neurodevelopment outcome (14)(15)(16)(17). Regaining of birthweight was much earlier in our study than previously reported.…”
Section: Discussionsupporting
confidence: 56%
“…Early introduction and faster advancement of feeds lead to a faster regaining of birthweight between 11 and 18 days (7,9,13). It also shows better catch-up growth, linear growth and neurodevelopment outcome (14)(15)(16)(17). Regaining of birthweight was much earlier in our study than previously reported.…”
Section: Discussionsupporting
confidence: 56%
“…The relationship between somatic growth and neurological outcome has not been fully investigated in infants with CHD, but has been well described in the preterm population [2527]. A slower growth velocity has been shown to increase the likelihood of neurodevelopmental impairment [25].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, they evaluated motor development using NSMDA and cognitive development using Griffhts Mental Development Scale in 197 babies. They showed that low body mass index of the babies born with a very low birth weight (<1 000 g) at the age of two years was related with low cognitive and motor skills (18). In another study in which the relation between early minor motor difficulties in babies born with a very low birth weight and attention difficulties in the school period was examined, a strong relation was found between attention in the school period and motor development at the age of 24 months according to NSMDA scores independent of biological and social factors in very low birth weight babies (19).…”
Section: Discussionmentioning
confidence: 99%